Molecular Detection of Clostridium-Related DNA in Bats from Soppeng, Indonesia - Muhammad Erwan Arifin; Syamsuar Manyullei; Anwar Mallongi; Erniwati Ibrahim; Apik Indarty Moedjiono (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Clostridium spp. are anaerobic, spore-forming bacteria widely distributed in soil, water, and the gastrointestinal tracts of humans and animals. Several species are associated with important human and veterinary diseases. Information regarding Clostridium-related bacteria in bats remains limited in Indonesia. This study aimed to generate preliminary molecular evidence of Clostridium-related bacterial DNA in bats from Soppeng Regency, South Sulawesi, Indonesia. Methods: Bat samples were collected in Soppeng Regency, South Sulawesi, Indonesia. Ten fruit bats (Cynopterus brachyotis) were captured near roosting and foraging sites, and three intestinal tissue samples were selected for molecular analysis based on sample integrity and DNA preservation quality. Genomic DNA was extracted using a commercial extraction kit following aseptic sample processing. Molecular detection was performed using PCR targeting the bacterial 16S rRNA gene, followed by agarose gel electrophoresis. PCR-positive amplicons were subjected to Sanger sequencing and analyzed using BLAST against the NCBI/GenBank database based on sequence identity, query coverage, and E-value. Results: All three analyzed samples produced positive amplification bands at the expected amplicon size of approximately 1,465 bp. BLAST analysis showed the closest sequence matches to Clostridium septicum (K1; 94% query cover; 97.57% identity; E=0.0), Paraclostridium sordellii (K3; 97% query cover; 96.64% identity; E=0.0), and Clostridium haemolyticum (K5; 95% query cover; 98.06% identity; E=0.0). Conclusion: This study provides preliminary molecular evidence of Clostridium-related bacterial DNA in fruit bats from Soppeng Regency. However, DNA detection alone does not confirm bacterial viability, pathogenicity, transmission potential, or reservoir status. Further studies involving culture confirmation, toxin gene characterization, environmental sampling, and broader wildlife surveillance are needed to clarify the ecological and public health significance of these findings.